Mechanism design and consumption certification of differentiated green electricity trading: A Zhejiang experience - Xu, Qifeng; Qiao, Songbo; Zhou, Huijie; Luo, Renjie; Ma, Xiangyu; Gong, Jianrong (Frontiers in Energy Research, 2022)
The carbon neutrality strategy marks that green electricity will replace fossil energy as the main power source in the future power system. The trading varieties in the electricity market will be more diverse, and the demand for green electricity by consumers will grow significantly. This paper innovatively proposes a provincial market framework for voluntary flexible trading of green electricity while elaborating on the conceptual design of differentiated green electricity trading processes in a systematic way for Zhejiang province. The proposed framework can not only reflect the carbon emission reduction attributes of green electricity but also fully exploit its commercial and social values. Moreover, the proposed green electricity trading certificate can realize the authoritative certification of green electricity consumption and help the construction of a carbon traceability mechanism. The proposed trading mechanism is expected to give rise to a new green electricity service industry and deepen the reform of the carbon and electricity synergy mechanism. The experience of green electricity trading in the Zhejiang province is expected to reveal the promotive impact of the electricity market on the carbon neutrality strategy.